What defines the “typical” sex offence perpetrated by juveniles in Iceland? : an analysis of their sexual offending behaviour - Anna Sofía Rosdahl 1993- (2017)
The aim of this study was to examine what characterizes juvenile sex offending in Iceland. This is a descriptive study based on pre-existing data on 92 juveniles reported to authorities for juvenile sex offending in 2012 to 2014, and their victims. A total of 112 cases were analysed. The reports were accessed through the Icelandic Police National Database. The majority of the offenders were male, aged of 11 to 17 at the time of the alleged offence. In most instances the offenders knew their victim. The findings demonstrated that it was more frequent that the reported offenders had residency outside the capital region. The juveniles were most often reported for sexual misconduct with a child under 15 years and rape. It was rare that the offenders and/or their victims were intoxicated when the alleged offence took place. In addition, the results demonstrated that the offenders showed low recidivism rates. Keywords: juvenile sex offenders, types of offence, residency, offence characteristics Markmið rannsóknarinnar var að kanna hvað einkennir helst unga kynferðisafbrotamenn á Íslandi sem og fórnarlömb þeirra. Rannsóknin var unnin með greiningu á rannsóknarskýrslum hjá 92 einstaklingum sem tilkynntir voru til lögreglunnar á árunum 2012 til 2014 fyrir kynferðisbrot framið fyrir 18 ára aldur, alls 112 mál. Meirihluti brotamannanna voru piltar sem brutu á stúlkum. Í flestum tilfellum þekkti brotamaður fórnarlamb sitt. Niðurstöður sýndu fram á að meirihluti afbrotamanna höfðu aðsetur utan höfuðborgarsvæðisins þegar meint brot átti sér stað. Algengast var að þessir einstaklingar væru tilkynntir fyrir nauðgun eða fyrir að hafa samræði við barn undir 15 ára aldri. Sjaldgæft var að brotaþoli og/eða þolandi væru undir áhrifum áfengis eða eiturlyfja þegar meint brot átti sér stað. Einnig sýndu niðurstöðurnar fram á að fátítt var að brotamennirnir frömdu fleiri en eitt kynferðisbrot. Lykilhugtök: ungir kynferðisbrotamenn, tegund kynferðisbrota, búseta, einkenni afbrota